Clove and Peppermint Essential Oils Effect on Pathogenic Gut Micro-Biota in Chronic Hepatic Disease Patients - Mohamed T Shaaban; Gehan M Fahmy; Esraa H Saad; Hussein S Salama (Pandawa Institute, 2024)
Multidrug-resistant bacteria infections in cirrhotic patients are currently increasing and associated with greater morbidity and mortality. The aim of this study was to decrease complications and bacterial infections that probably occurred after a patient undergoes liver transplantation surgery in Egypt using natural edible nontoxic peppermint and clove essential oils. All patients undergo clinical, laboratory, and microbiological testing. The recorded results showed that administered minimum inhibitory concentration (MIC) of clove and peppermint essential oils significantly reduced the total colony forming unit (CFU) count of multidrug-resistant pathogenic bacteria isolated from patients with chronic hepatic disease. The gas chromatography-mass spectrometry (GC-MS) analysis of clove and peppermint oil revealed the presence of active constituents with antibacterial activities as indicated in previous reviews.